I am a bird - Lim, Hope (Candlewick Press, 2021)
Each morning, a little girl and her dad ride their bike to school. As they twist and turn through the city streets, the little girl sings her bird song for all to hear. But when the girl sees the strange woman in blue carrying a mysterious bag, she goes quiet until the woman is out of sight. One day, when the little girl and her dad are running late, the girl discovers what the woman in blue does with her bag each morning. The surprising revelation transforms the girl's fear of the stranger into a kinship to be celebrated.